Severity of Rhizoctonia root rot in beans influenced by liming, nitrogen sources and rates - Rodrigues, Fabrício de Ávila; Carvalho, Enia Mara; do Vale, Francisco Xavier Ribeiro (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this study was to determine the effects of liming, nitrogen sources and rates on the severity of Rhizoctonia root rot (RRR) in beans under controlled conditions. In the first experiment, the soil was amended with 0, 1.75, 2.25, 2.75, 3.25 and 3.75 g of dolomitic lime per kilogram of soil. In the second experiment, the soil was fertilized with 0, 11, 16, 21, 26 and 31 mg N kg-1 of soil, using ammonium sulfate and sodium nitrate as N sources. For the second experiment, soil acidity was adjusted by applying 1.75 g of dolomitic lime per kilogram of soil. Both experiments were arranged in a completely randomized design, with five replications. Soil was infested before sowing with 16 g of rice grains infested by Rhizoctonia solani per kilogram of soil. Twenty-five days after seed germination, the severity of RRR was evaluated based on lesion development on the hypocotyls, by using a scale ranging from 0 to 5. Data obtained were used to calculate the disease index (DI, %). Linear equations significantly described liming and N source-severity of RRR relationships. Liming increased DI by 32% over the control. After liming, application of ammonium sulfate reduced DI by 22%, while sodium nitrate increased DI by 18%, over the control.